DOI: 10.15368/theses.2016.60
|View full text |Cite
|
Sign up to set email alerts
|

Diagonal Tension Testing of Interlocking Compressed Earth Block Panels

Abstract: This thesis examines the use of diagonal tension (shear) testing to determine factors affecting shear strength of Interlocking Compressed Earth Block (ICEB) panels. This work expands on the current information available about strength properties of ICEB assemblies, which are dry-stacked, as opposed to having mortared beds. Variables such as block strength, grout strength and grouting pattern can influence the results of these types of tests and are examined in this investigation.To study variables affecting di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 8 publications
1
8
0
Order By: Relevance
“…This artificially increases the block's strength compared to the completely unconfined failure that would take place in a full-scale stack of blocks. It also causes a characteristic conical failure visible in Figure 3.19 that has been widely observed by past research, including Bland (2011) and Pringle (2016). These testing artifacts can be overcome with prism tests.…”
Section: Compressive Strengthmentioning
confidence: 68%
See 4 more Smart Citations
“…This artificially increases the block's strength compared to the completely unconfined failure that would take place in a full-scale stack of blocks. It also causes a characteristic conical failure visible in Figure 3.19 that has been widely observed by past research, including Bland (2011) and Pringle (2016). These testing artifacts can be overcome with prism tests.…”
Section: Compressive Strengthmentioning
confidence: 68%
“…Previous research (Bland, 2011) has indicated that directly applying existing code-based masonry design equations dramatically over-predicts the in-plane shear capacity of interlocking compressed earth block walls. The research in this thesis continues prior work examining the in-plane lateral capacity of full-scale walls (Bland, 2011;Stirling, 2011) as well as research on factors specifically affecting shear capacity (Pringle, 2016).…”
Section: Introductionmentioning
confidence: 76%
See 3 more Smart Citations